Application of multiplication method using multiplication board to elementary school students - Adelya Putri, Barika; Zamhari, Ahmad; Laily, Isyroh; Resti Paramita, Dyah; Furwanti, Elsy (ARKA INSTITUTE, 2023)
In order to meet the development of mathematics learning in elementary school children, we find and form media to improve the material to make it easier for students to learn, therefore we create learning media namely